The Jack-in-the-Box: Pericardial Decompression Syndrome Managed by a Multidisciplinary Approach with Early Initiation of Veno-Arterial Extracorporeal Membrane Oxygenation: A Case Report - Carmen Orban; Tudor Borjog; Claudia Talpau; Mihaela Agapie; Angelica Bratu; Mugurel Jafal; Mihai Popescu (Medicina)
Post decompression syndrome (PDS) is a rare and life-threatening complication of pericardiocentesis, especially after rapid drainage of large amounts of pericardial fluid. We present the case of a 21-year-old man who presented with cardiac tamponade of unknown etiology. After preoperative optimization, surgical drainage of the pericardial effusion was performed and approximately 2500 mL of fluid was released over 30 min. The patient rapidly developed hemodynamic collapse with severe biventricular dysfunction, with a left ventricle ejection fraction of 15%. Vasopressor and inotropic support were initiated with Noradrenaline and Dobutamine, further escalated to Adrenaline and Levosimendan with no improvement in clinical and hemodynamic parameters. Considering the high doses of vasoactive drugs, rescue veno-arterial extracorporeal membrane oxygenation (V-A ECMO) was started within the first 24 h. After 10 days on V-A ECMO, the cardiac function slowly recovered, and the extracorporeal mechanical support was successfully weaned. The diagnosis of paraneoplastic PDS secondary to angiosarcoma was made and the patient was successfully discharged to the ward on the 24th day. In conclusion, far from being the last option in the management of PDS, V-A ECMO deserves early consideration for securing adequate myocardial and systemic perfusion, while the cardiac function recovers, but a risk-to-benefit assessment should be made by an experienced multidisciplinary team.